Exploring autonomy support and learning preference in higher education: introducing a flexible and personalized learning environment with technology - Atsunori Fujii (Springer, 2024)
Abstract Learner autonomy is particularly important in higher education, where students are fully responsible for their own learning. Despite this, there is a lack of research on aspects of autonomy support in higher education compared with that of primary and secondary education. To address this gap, this study explored autonomy support and learning preference in higher education, introducing a flexible and individualized learning environment with technology after the COVID-19 pandemic. A survey was conducted among 849 Japanese university students to gather their perceptions about autonomous support, learning preferences (face-to-face or distance), use of learning strategies, and academic performance (grade point average). Correlations were identified between certain variables: for example, perceived autonomy support, class format preference, and grade point average. The scores of different scales were compared among the subject groups. Autonomy support provided by instructors included explaining the lesson's outline to students. A few teachers provided opportunities for students to select learning methods, teaching materials, and assignment content; yet, few instructors seemed to truly understand students' learning needs. Although many participants took face-to-face courses, students' learning preferences were evenly split between face-to-face and distance learning courses. Students who strongly preferred face-to-face learning performed well regardless of instructional format. Students with a little preference for distance education performed well, especially in distance education courses. Students with no preference performed the worst. This study suggests that a learning environment that provides students with options to suit their diverse learning preferences is beneficial and that introducing "hybrid-flexible" courses and feedback for students' learning strategies has the potential to promote learner autonomy in higher education.